Beginnings of open-heart surgery in Gdansk – double role of the Pemco heart-lung machine and new facts about Dutch-Polish cooperation - Paprocka-Lipińska, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The first open-heart surgery in Gdansk took place in 1975. It was possible thanks to the gift of a Pemco extracorporeal circulation machine from the Netherlands to the Surgery Institute of the Medical Academy of Gdansk. The article presents additional, unpublished informations which enable a new interpretation of the previously known facts.